CP-009 Impact of pharmaceutical intervention on quality of life and coping strategies in patients with haematological malignancies. (24th March 2015) - Opsomer, M; Anota, A; Noblot-Rossignol, M; Bonnetain, F; Pernot, C; Chretien, M; Legouge, C; Caillot, D; Boulin, M
Abstract : Background: Chemotherapy especially that used in Haematological Malignancies (HMs) has severe biological and clinical adverse effects (AEs). Such symptoms often impair patients' quality of life (QoL). Adjuvant drugs are prescribed to patients to prevent these AEs. For patients at home, taking these adjuvant drugs is complicated because of the different regimens: only if necessary (antiemetics), only in the presence of symptoms such as fever (antibiotics), etc. Purpose: In our hospital, patients receiving their first chemotherapy for an HM benefit from a pharmaceutical intervention (PI). We conducted a prospective study approved by the local ethics committee to determine the impact of the PI on pain, fatigue, QoL and coping strategies in patients undergoing chemotherapy for an HM. Material and methods: Patients received either usual care (UC) + PI (PI group) or UC alone (UC group). They had to complete the QLQ-C30 and MAC 21 questionnaires before starting the 1st chemotherapy session (T1), during the inter-treatment interval (T2) and the day before starting the 2nd chemotherapy session (T3). To determine predictive factors of pain, fatigue and QoL at T3, a univariate followed by a multivariate ANOVA was used. The time until definitive deterioration was estimated using a Kaplan-Meier method. Results: 68 patients were included in the PI (n = 34) or UC groups (n = 34). Ninety-two percent of the patients returned all the questionnaires. At T3, pain and fatigue were lower in the PI group. Between T1 and T3, QoL remained stable. We identified a significant improvement of 5 points in QoL for patients in the PI group. Conclusion: Whatever the statistical model used, the pharmacist intervention at the beginning of chemotherapy had a less than significant impact on pain and fatigue but nevertheless it was confirmed to have had a significantly positive impact on QoL. References and/or acknowledgements: The authors thank Philip Bastable. No conflict of interest.